INSTALASI PEMBANGKIT LISTRIK TENAGA SURYA UNTUK KELOMPOK PETERNAK MUDA DESA UNGGUL FARM, DESA PANDAK KECAMATAN BALONG KABUPATEN PONOROGO - Khoirudin Asfani; Langlang Gumilar; Quota Alief Sias; Wahyu Nur Hidayat (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract The sector in Indonesia is currently being optimized as a source of income and welfare for local communities. The government targets, at least there is an increase in the quality of the poultry farming business in order to achieve the welfare of the local community and open up business opportunities for the surrounding population. To achieve this, one way that needs to be done is an assessment of the pillars of the livestock business (farm business sustainability). One of the local community-based livestock business groups that is developing and has the potential to develop potential in the field of entrepreneurship and employment is the Kelompok Peternak Muda Desa Unggul Farm in Ponorogo. In order to realize a livestock business with community and local community empowerment programs, field observations were carried out as a form of fulfilling preliminary studies in carrying out Community Service activities. In its development, several shortcomings are currently being experienced, namely: 1) there is no solar power plant for the lighting needs of poultry farms and 2) there is no adequate human resources to utilize and maintain the electric power generation system. The proposed activity plan consists of several stages. These stages are passed sequentially and in parallel consisting of: 1) the stage of literature study; 2) stages of data collection; 3) the planning stages of the PV mini-grid system; 4) the installation and trial stages of the PV mini-grid system; and 5) PV mini-grid system maintenance training. Through Community Service, this activity seeks to provide a product in the form of a Solar Power Plant system that can be useful for the Kelompok Peternak Muda Desa Unggul Farm in Ponorogo as an alternative energy source and provide additional insight regarding the use of renewable energy. Abstrak Sektor peternakan di Indonesia saat ini sedang dioptimalkan sebagai sumber pendapatan dan kesejahteraan bagi masyarakat lokal. Pemerintah menargetkan, setidaknya ada peningkatan kualitas usaha bidang peternakan unggas guna mencapai kesejahteraan masyarakat lokal dan membuka peluang usaha bagi penduduk sekitar. Untuk mencapainya, salah satu cara yang perlu dilakukan adalah peningkatan penilaian untuk pilar keberlanjutan usaha ternak (farm business sustainability). Salah satu kelompok usaha ternak berbasis masyarakat lokal yang sedang berkembang dan memiliki potensi untuk dikembangkan potensi lokal bidang kewirausahaan dan lapangan kerja adalah Kelompok Peternak Muda Desa Unggul Farm di Kabupaten Ponorogo. Guna mewujudkan pengembangan usaha ternak dengan program pemberdayaan masyarakat dan komunitas lokal, maka dilakukan observasi lapangan sebagai bentuk pemenuhan studi pendahuluan dalam melaksanakan kegiatan PKM. Dalam pengembangannya, beberapa kekurangan saat ini tengah dialami, yaitu: 1) belum adanya pembangkit listrik tenaga listrik (PLTS) untuk kebutuhan tenaga penereangan ternak unggas dan 2) belum adanya SDM yang memadai untuk memanfaatkan dan memelihara system pembangkit listrik tenaga listruk. Rencana kegiatan yang diusulkan terdiri dari beberapa tahapan. Tahapan-tahapan tersebut dilalui secara sekuensial dan paralel yang terdiri dari: 1) tahapan studi literatur; 2) tahapan pengumpulan data; 3) tahapan perencanaan sistem PLTS; 4) tahapan pemasangan dan uji coba sistem PLTS; dan 5) tahapan pelatihan pemeliharaan system PLTS. Melalui PKM, kegiatan ini berupaya untuk memberikan produk berupa sistem PLTS yang dapat bermanfaat bagi Kelompok Peternak Muda Desa Unggul Farm di Kabupaten Ponorogo sebagai sumber energi alternatif dan memberikan wawasan tambahan terkait pemanfaatan energi terbarukan.